2023
DOI: 10.3390/life13020332
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Benefits of Banana Phenolic Content during Ripening by Implementing Analytical and In Silico Techniques

Abstract: Banana ranks as the fifth most cultivated agricultural crop globally, highlighting its crucial socio-economic role. The banana’s health-promoting benefits are correlated with its composition in bioactive compounds, such as phenolic compounds. Thus, the present study attempts to evaluate the potential health benefits of banana phenolic content by combing analytical and in silico techniques. Particularly, the total phenolic content and antioxidant/antiradical activity of banana samples during ripening were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The findings indicated that green pulp had a higher total phenolic content (TPC) than ripe pulp. This finding was consistent with the other study's finding that banana pulp's TPC reduced as fruits ripened (Kritsi et al, 2023). The primary bioactive components of banana fruits are phenolic compounds, which provide antioxidant, anti-inflammatory, anticancer, antimicrobial, anti-inflammatory, antidiabetic, and anti-allergic activities (Moo-Huchin et al, 2015;Islam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings indicated that green pulp had a higher total phenolic content (TPC) than ripe pulp. This finding was consistent with the other study's finding that banana pulp's TPC reduced as fruits ripened (Kritsi et al, 2023). The primary bioactive components of banana fruits are phenolic compounds, which provide antioxidant, anti-inflammatory, anticancer, antimicrobial, anti-inflammatory, antidiabetic, and anti-allergic activities (Moo-Huchin et al, 2015;Islam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The portion of BP that is edible is rich in nutrients. Depending on their chemical makeup, BP and its flour may have a variety of purposes (Kritsi et al, 2023). Banana peel suggests a possible better value in terms of antioxidant content because a prior study found that the antioxidant chemicals in the peel were higher than in the pulp (Parvez et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…MS acquisition was performed with an electrospray (ESI) ionization source in the negative mode, which is the preferred ionization mode for the phenolic compounds. Moreover, the data-dependent MS/MS analysis was conducted by applying information-dependent acquisition (IDA)-triggered MS/MS scans (EPI—enhanced product ion scans) [ 29 ]. The mass error was 0.1 Da in MS and 0.5 Da in MS/MS.…”
Section: Methodsmentioning
confidence: 99%
“…The mass error was 0.1 Da in MS and 0.5 Da in MS/MS. All the technical and instrumentation-related information regarding the LC-MS/MS method used for the elucidation of the phenolic compounds of coffee samples are described in detail in previous publications of our group [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation